(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Health Sciences Series, 2026)
Fine manual dexterity declines in most elderly people due to changes in the functions of various body systems. This study was conducted with the aim of evaluating fine manual dexterity among elderly people residing in nursing homes in Lattakia, during the period from (15/8/2024 to 15/11/2024) on a sample of 30 elderly people residing in nursing homes, who were selected by simple random method. The study data were collected using two tools: the demographic data form for the elderly and the fine manual dexterity scale. The study concluded that all elderly residents in nursing homes had a decline in fine manual dexterity performance of both the dominant and non-dominant hand. Therefore, it is recommended to conduct training programs for elderly people residing in nursing homes to improve fine manual dexterity in the elderly, and to conduct a study to evaluate the effect of motor rehabilitation programs on fine manual dexterity in the elderly.